Haasea Verhoeff, 1895—a genus of tumultuous history and chaotic records—redefinition, revision of taxonomy and geographic distributions, with descriptions of two new species from Austria and Serbia (Diplopoda, Chordeumatida, Haaseidae) - Antić, Dragan; Akkari, Nesrine (Zootaxa, 2020)
In this paper we revise the chordeumatidan genus Haasea Verhoeff, 1895 for the first time and describe two new species viz., H. gruberi sp. nov. and H. makarovi sp. nov. discovered in Austria and Serbia, respectively. A new terminology is proposed to standardize the description of the gonopod structures in the genus. Type material obtained from several institutions was examined and documented herein, whereby lectotypes are designated. We clarified the taxonomic status of a few taxa and consider the species H. norica (Verhoeff, 1913) and H. guidononveilleri Makarov, 2008 as a junior subjective synonyms of H. cyanopida (Attems, 1903) and H. vidinensis (Strasser, 1973a), respectively. The following subspecies or varieties, viz., Orobainosoma filicis ossiacum Verhoeff, 1939b, Orobainosoma flavescens vornatscheri Verhoeff, 1935, Orobainosoma hungaricum orientale Tabacaru, 1965, and Orobainosoma inflatum var. aspidiorum Verhoeff, 1929 are here regarded as junior subjective synonyms of their nominal taxa. The taxonomic relationships within the genus Haasea are discussed and an identification key to its 17 species is presented, based on number of body segments and gonopod structures.                Maps showing species occurences based on historical and recent records are presented to understand their respective geographic ranges. H. flavescens is now deleted from the list of species in Croatia, Bosnia and Herzegovina, Slovenia and Italy as these records were based on misidentified material. H. inflata is deleted from the fauna of Bosnia and Herzegovina, whereas H. hungarica is newly recorded from Austria, Serbia and Slovenia.